Pengaruh Persepsi Manfaat dan Persepsi Risiko terhadap Kelanjutan Penggunaan E-wallet Gopay dengan Kepercayaan sebagai Variabel Mediasi - Sarah Setyaningrum; Dwi Eko Waluyo (LPPM Politeknik Pratama, 2025)
The purpose of this study is to analyze the effect of perceived benefits and perceived risks on the continued use of the Gopay e-wallet, with trust as a mediating variable. Data were collected through questionnaires using purposive sampling method, with 213 respondents as samples. The SEM-PLS method was applied in data analysis using SmartPLS software version 4.1.0.9. The results of this study are (1) perceived benefits have a positive and significant effect on the continued use of the Gopay e-wallet, (2) perceived risk does not have a significant effect on the continued use of the Gopay e-wallet, (3) trust has a positive and significant effect on the continued use of the Gopay e-wallet, (4) perceived benefits have a significant positive effect on the continued use of the Gopay e-wallet through trust, (5) perceived risk also has a significant positive effect on the continued use of the Gopay e-wallet through trust.